Japan’s second world war victory: an analysis of the reaction of the japanese immigrants in Brazil to japanese defeat (Dialogos, 2017)
Em Agosto de 1945 a rendição incondicional do Japão foi muito anunciada pela mídia brasileiros, mas para a grande maioria dos imigrantes Japoneses e dos seus descendentes a guerra tinha acabado mas o Japão não tinha sido derrotado. Contudo, nem todos concordavam e alguns deles reconheceram a derrota do Japão. Os Japoneses no Brasil dividiram-se então em duas facções e a confusão varreu as suas comunidades. O principal argumento apresentado neste artigo é que o conflito inter-grupal que dividiu os Japoneses no Brasil no período imediatamente a seguir Ã  guerra tem de ser compreendido no contexto da constelação de forças econômicas e sociais nas comunidades assim como no contexto histórico das forças que moldaram a vida dos imigrantes Brasileiros durante grande parte do período anterior Ã  guerra.Abstract. In August 1945 Japan’s unconditional surrender was widely reported by the Brazilian media but for the vast majority of Japanese immigrants and their descendants the war was over but Japan had not been defeated. However, not everyone was in agreement and some of them did recognise the defeat of Japan. The Japanese in Brazil were then split into two factions and confusion swept their communities. The main argument advanced in this article is that the inter-group conflict that divided people of Japanese descent in Brazil immediately after the war is to be understood in the context of a constellation of economic and social forces at work in the Japanese communities as well as in the historical context of forces that shaped the life of Japanese immigrants for much of the pre-war period.